Academic inbreeding in the Spanish public university system: a review of its institutional and context determinants (Endogamia en el sistema universitario público español: una revisión de sus determinantes institucionales y contextuales). Issue 2 (3rd April 2021) - de la Torre, Eva M.; Perez-Esparrells, Carmen; Romero-Madrid, Teresa
ABSTRACT: University systems with a high level of academic inbreeding tend to be closed to attracting (inter)national talent, while instead prioritizing retention of the human factor in the institution and the stabilization and continuity of internal bureaucratic dynamics. The literature suggests that levels of academic inbreeding depend on both institutional and structural factors within the universities themselves, as well as contextual factors in the country and/or region. In this study, we empirically analyse the causal relationship between levels of academic inbreeding at Spanish public universities and the characteristics of the university context and their institutional features. Our results show that the variables that most influence the level of endogamy of Spanish public universities are their age and their specialization by field of knowledge. Furthermore, the academic inbreeding in Spain seems more related to the chair-holding dynamics by which professors gain power than to any other factor.